Implant placement with maxillary lateral window sinus lifting: Pemasangan implan disertai sinus lifting dengan teknik lateral window - Ratna Sari dewi; Djamilah Tohirah dewi (Makassar Dental Journal PDGI Makassar, 2023)
Abstract. Dental implant are becoming more popular option for permanent teeth replacement in this new era. However, in some cases we can’t use favorable implants in the maxillary premolar and molar region. This is because atrophy is observed following tooth extraction in this region. Sinus lift procedures are a commonly accepted method of bone augmentation in the lateral maxilla which aims to increased vertical bone high volume in the maxillary sinus by lifting the lower alveolar bone height and placing or without placing a bone graft in order to enable installation of dental implants preparation with clinically good results. Sinus lifting with the lateral window technique are one of the methods to correct the height of inadequate bone in the posterior area of maxilla for preparation of dental implant insertion. Dental implant placement with sinus lifting lateral window technique can be performed in 1 or 2 surgical stages depending on the residual alveolar bone height. The aim of this article was to describe the surgical procedure of sinus lifting with lateral window technique to enable preparation the installation of dental implant based on review the literature by several researchers in years 2007 – 2021. Conclusions: Dental Implant placement procedure with sinus lifting lateral window technique has a high survival rate although it is not possible to identify it’s correct indication and contraindication. Within the limitations of this review literature practicioners should select the adequate type of procedure and needed concidering anatomical variation of the sinus maxillaris Abstrak. Pada periode masa baru ini dental implant menjadi pilihan popular untuk menggantikan gigi asli yang hilang. Namun, pada beberapa kasus kita tidak dapat melakukan pemasangan implant pada maksila di regio molar dan premolar. Hal ini disebabkan adanya atrofi yang terjadi pada daerah tersebut akibat ekstraksi gigi. Prosedur sinus lifting adalah metode bone augmentation pada bagian lateral maksila yang secara umum dapat diterima dan tujuannya adalah untuk meningkatkan volume tinggi tulang vertikal pada sinus maksilaris dengan cara menempatkan atau tanpa menempatkan cangkok tulang pada tulang alveolar yang rendah untuk persiapan pemasangan implant dan secara klinis memberikan hasil yang baik. Sinus lifting dengan teknik lateral window adalah salah satu metode untuk koreksi tinggi tulang yang tidak memadai pada daerah posterior maksila untuk persiapan pemasangan implant. Pemasangan implant dengan sinus lifting teknik lateral window dapat dilakukan dalam 1 atau 2 tahap operasi tergantung dari sisa tinggi tulang alveolar. Tujuan penulisan artikel ini adalah untuk menjabarkan prosedur sinus lifting dengan teknik lateral window untuk persiapan pemasangan implant berdasarkan tinjauan literatur beberapa peneliti dari tahun 2007 – 2021. Kesimpulan: prosedur pemasangan implant disertai sinus lifting dengan teknik lateral window rata-rata memberikan hasil yang tinggi walaupun sulit untuk identifikasi indikasi dan kontraindikasi yang tepat. Dalam keterbatasan dari tinjauan pustaka ini, para praktisi harus dapat memilih prosedur yang tepat dan mampu memperhatikan anatomi dari sinus maksilaris.